Mental health problems and coping strategies of elementary teachers - Akmad, Rahima Adal; Latip, Bai Rhea A.; Kadtong, Maeda Langguyuan; Nilong, Datu Joharie B.; Daglok, Sittie Rahema T. (Edelweiss Applied Science and Technology, 2025)
This study aims to determine the mental health problems and coping strategies of elementary teachers at selected schools of Datu Anggal Midtimbang District, Philippines. The study utilized quantitative research and survey questionnaire as instrument. The study conducted at selected schools of Datu Anggal Midtimbang District namely: Bai Salud Elementary School, Mapayag Elementary School and Kiteb Central Elementary School with complete enumeration was used to choose the fifty (50) respondents. The frequency count like mean was used to interpenetrate the data. The result of the study presents that respondents perceived that in terms of depression, sleep disturbance and loss interest are very often a problem justified by the mean of 2.54. In terms of stress, respondents stressed that very often they had sleep disorders justified by the mean of 2.56. They also manifested that overeating/under eating is rarely problem if they are stress justified by the mean of 2.41. For anxiety, respondents stressed that feeling weak or tired very often a problem they experienced with mean of 2.49. Furthermore, the increased heart rate a rarely a problem to them with mean of 1.92. In terms of grief, sleep disturbance rarely a problem they perceived with mean of 2.26. Moreover, the bitterness about the loss also rarely a problem they perceived with mean of 1.98. The coping strategies mental health problems were as follows like meditate or pray to overcome depression, keeping a positive attitude, talking with love ones, practiced exercising, seek out support and reading self-help books.